Woodland strawberry axillary bud fate is dictated by a crosstalk of environmental and endogenous factors. Issue 3 (1st September 2021) - Andrés, Javier; Caruana, Julie; Liang, Jiahui; Samad, Samia; Monfort, Amparo; Liu, Zhongchi; Hytönen, Timo; Koskela, Elli A
Abstract: Plant architecture is defined by fates and positions of meristematic tissues and has direct consequences on yield potential and environmental adaptation of the plant. In strawberries ( Fragaria vesca L. and F . × ananassa Duch.), shoot apical meristems can remain vegetative or differentiate into a terminal inflorescence meristem. Strawberry axillary buds (AXBs) are located in leaf axils and can either remain dormant or follow one of the two possible developmental fates. AXBs can either develop into stolons needed for clonal reproduction or into branch crowns (BCs) that can bear their own terminal inflorescences under favorable conditions. Although AXB fate has direct consequences on yield potential and vegetative propagation of strawberries, the regulation of AXB fate has so far remained obscure. We subjected a number of woodland strawberry ( F. vesca L.) natural accessions and transgenic genotypes to different environmental conditions and growth regulator treatments to demonstrate that strawberry AXB fate is regulated either by environmental or endogenous factors, depending on the AXB position on the plant. We confirm that the F. vesca GIBBERELLIN20-oxidase4 ( FvGA20ox4 ) gene is indispensable for stolon development and under tight environmental regulation. Moreover, our data show that apical dominance inhibits the outgrowth of the youngest AXB as BCs, although the effect of apical dominance can be overrun by the activity of FvGA20ox4 . Finally, we demonstrate that the FvGA20ox4 is photoperiodically regulated via FvSOC1 ( F. vesca SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 ) at 18°C, but at higher temperature of 22°C an unidentified FvSOC1 -independent pathway promotes stolon development. Abstract : Environmental conditions and apical dominance dictate woodland strawberry plant architecture by regulating axillary bud fate.